Experimental Study on Mineral Solid Waste Green Grouting Material Based on Electromagnetic Characteristic Detection - Xiangpeng Wang; Jin Hu; Xiang Zhang; Kunpeng Wang; Di Shen; Chuntao Liang (Advances in Civil Engineering)
The production processes for the gypsum- and cement-based materials, which are widely used in civil engineering projects, require the consumption of large amounts of energy and natural resources. At the present time, the main development directions of civil engineering material include realizing solid waste recycling and the applications of green building materials, which can be then used in the fields of disaster treatment and ecological restoration, such as grouting materials. In addition, the grouting quality is always difficult to detect. This study examined the gypsum- and cement-based green grouting materials made from mineral solid waste used in disaster and cloud detection by means of electromagnetic characteristics. According to the requirements of electrical testing of grouting quality, first we designed a material made with solid waste. Then, we studied the resistivity, strength, porosity, and other physical and mechanical properties of the material. The test results of the material and its soaking solution indicate that this material is a green material meeting the environmental safety standards. The experimental results show that the rapid detection of grouting quality can be realized. The following effects on electromagnetic characteristics and mechanical properties of the green materials of gypsum- and cement-based were analyzed. The results showed that the resistivity and strength were related to the ratios of the water content to the modified phosphogypsum; the percentages of cement content in the total amount of modified phosphogypsum and marble powder; the percentages of marble powder in the modified phosphogypsum; the percentages of steel fiber content in the phosphogypsum; and the fineness of the marble powder. The field test results also confirm that the green grouting material can be effectively applied in engineering repair imaging monitoring.